OUTCOME OF ISOLATED FETAL ASCITES AND ETIOLOGY : A SYSTEMATIC REVIEW - Fahrozy, Akhmad (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Isolated fetal ascites is defined as fluid accumulation in the abdominal cavity without fluid accumulation in any other serosal cavities or subcutaneous tissues, being therefore a distinct entity from hydrops fetalis. It is a rare ultrasound (US) finding that is always considered abnormal and should be thoroughly investigated. The aim: This study aims to show about etiology and outcome of isolated fetal ascites. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 115 articles, whereas the results of our search on SagePub brought up 156 articles. The results of the search conducted for the last year of 2013 yielded a total 42 articles for PubMed and 78 articles for SagePub. The result from title screening, a total 3 articles for PubMed and 14 articles for SagePub. In the end, we compiled a total of 7 papers. We included five research that met the criteria. Conclusion: The natural history of this condition remains unclear, despite the fact that immune and nonimmune hydrops are well described and documented. Reported causes of isolated fetal ascites are cardiac, renal, gastrointestinal, pulmonary, and metabolic disorders. Infectious diseases may be related to fetal ascites.